2007
DOI: 10.1103/physreve.76.032101
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsically anomalous self-similarity of randomly folded matter

Abstract: We found that randomly folded thin sheets exhibit unconventional scale invariance, which we termed as an intrinsically anomalous self-similarity, because the self-similarity of the folded configurations and of the set of folded sheets are characterized by different fractal dimensions. Besides, we found that self-avoidance does not affect the scaling properties of folded patterns, because the self-intersections of sheets with finite bending rigidity are restricted by the finite size of crumpling creases, rather… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
59
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(63 citation statements)
references
References 30 publications
2
59
2
Order By: Relevance
“…More recently, it was found that the internal structure of folding configurations also possesses scaling invariance within a wide range of length scales [43]. The fractal dimension of folding configurations is found to be universal 05 .…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…More recently, it was found that the internal structure of folding configurations also possesses scaling invariance within a wide range of length scales [43]. The fractal dimension of folding configurations is found to be universal 05 .…”
Section: Introductionmentioning
confidence: 99%
“…The fractal scaling behavior (2) was observed in numerous experiments with randomly folded papers [35,37,43,47,51,52,53,54,55,56], metal foils [18,35,42,57,58], and cream layers [38].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations